Freshwater, Terrestrial, and Marine Turtles of Florida - Patricia Sprott; Frank J. Mazzotti; Jocie A. Graham (EDIS)
Florida is home to 25 species of turtles representing seven families. Turtles (including tortoises and terrapins) can be terrestrial, aquatic, or semi-aquatic. In aquatic food pyramids, some turtles are top carnivores since they feed on other small aquatic animals and rarely become food themselves. Like other reptiles, turtles are poikilothermic (dependent on their surroundings for their body temperature). This document is WEC-173, one of a series of the Department of Wildlife Ecology and Conservation, University of Florida, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences. Published:1993, as SS-WIS-57. Revised: November, 2003.